Money talks: performance-based reimbursement systems impact on perceived work, health and patient care for physicians in Sweden - Brulin, Emma; Ekberg, Kerstin; Landstad, Bodil J.; Lidwall, Ulrik; Sjöström, Malin; Wilczek, Alexander (Frontiers in Psychology, 2023)
The study aimed to investigate in which way the performance-based reimbursement (PBR) systems in Swedish healthcare services 1) subjectively impacted physicians' work and patient care and 2) were associated with the occurrence of stress-induced exhaustion disorders among physicians.The study applied a mixed-method design. Data were collected from a representative sample of Swedish physicians. In the questionnaire, respondents were asked to answer an open-ended question regarding their reflections on PBR. The answers to the open-ended question were analysed using thematic analysis. Respondents were also asked to rate the impact of PBR on their work. The association between PBR and self-rated stress-induced exhaustion disease was analysed with logistic regressions. Stress-induced exhaustion disorder was measured using the Burnout Assessment Scale. Thematic analysis resulted in 4 themes: 1) Money talks 2) Patients are affected 3) Medical morals are challenged 4) PBR increase the quantity of illegitimate tasks. Logistic regressions showed that physicians who experienced PBR had an impact on their work and had a two-fold higher risk of stress-induced exhaustion disorder. Our findings suggest that current reimbursement systems in Sweden play an essential role in Swedish healthcare and negatively influence physicians' work and health. Also, current PBR impact patients negatively. No previous study has explored the potentially harmful impact of PBR on how physicians perceive work, health and patient care. Results indicate that policymakers should be encouraged to deeply review PBR systems and focus on ways that they can limit the negative impact on physicians' work and health while meeting future challenges.